Field—Based Supercritical Fluid Extraction of Hydrocarbons at Industrially Contaminated Sites - Peggy Rigou; Steven John Setford; Selwayan Saini (The Scientific World Journal)
Examination of organic pollutants in groundwaters should also consider the source of the pollution, which is often a solid matrix such as soil, landfill waste, or sediment. This premise should be viewed alongside the growing trend towards field-based characterisation of contaminated sites for reasons of speed and cost. Field-based methods for the extraction of organic compounds from solid samples are generally cumbersome, time consuming, or inefficient. This paper describes the development of a field-based supercritical fluid extraction (SFE) system for the recovery of organic contaminants (benzene, toluene, ethylbenzene, and xylene and polynuclear aromatic hydrocarbons) from soils. A simple, compact, and robust SFE system has been constructed and was found to offer the same extraction efficiency as a well-established laboratory SFE system. Extraction optimisation was statistically evaluated using a factorial analysis procedure. Under optimised conditions, the device yielded recovery efficiencies of >70% with RSD values of 4% against the standard EPA Soxhlet method, compared with a mean recovery efficiency of 48% for a commercially available field-extraction kit. The device will next be evaluated with real samples prior to field deployment.